(untitled) (Conferencea, 2023)
The article analyzes the approach to creating comfortable conditions for pedestrians and tourists by air control in pedestrian areas in countries with extreme climates of the world. Also, the proposal presents the historical experience of providing moderate climatic conditions in open and closed areas of Uzbekistan and the example of the tourist centers of the city of Khiva in the current urban planning practice.